2000
DOI: 10.1002/1097-0029(20000815)50:4<268::aid-jemt3>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

LDL receptor-related protein (LRP) in Alzheimer's disease: Towards a unified theory of pathogenesis

Abstract: To date, mutations in three genes, β‐amyloid precursor protein (APP), presenilin 1 (PS1), and presenilin 2 (PS2), have been found to be causally related to familial Alzheimer's disease (AD). In addition, polymorphisms in three other genes (among others), apolipoprotein E (apoE), alpha2‐macroglobulin (αm), and the low density lipoprotein receptor‐related protein (LRP), are implicated to contribute to AD pathogenesis. Interestingly, the encoded gene products are all functionally related in various ways to LRP. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 112 publications
(123 reference statements)
0
15
0
Order By: Relevance
“…LRP is a neuronal receptor for several ligands believed to be important in AD pathogenesis including apolipoprotein E (apoE) and APP (14,27). Here, we showed that neuronal overexpression of a functional minireceptor of LRP (mLRP2) increased soluble levels of brain A␤ in PDAPP mice in an age-dependent manner.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…LRP is a neuronal receptor for several ligands believed to be important in AD pathogenesis including apolipoprotein E (apoE) and APP (14,27). Here, we showed that neuronal overexpression of a functional minireceptor of LRP (mLRP2) increased soluble levels of brain A␤ in PDAPP mice in an age-dependent manner.…”
Section: Discussionmentioning
confidence: 92%
“…LRP is an Ϸ600-kDa cell-surface endocytic receptor member of the LDL receptor family (13). LRP is highly expressed in the brain and is considered the major neuronal receptor for apolipoprotein E (apoE) and ␣ 2 -macroglobulin (␣ 2 M), also implicated in the pathogenesis of AD by both biochemical and genetic evidence (14).A putative role for LRP in AD is supported by in vitro studies showing that apoE and ␣ 2 M can form stable complexes with A␤ and promote its clearance via cell-surface LRP (5-10). Furthermore, LRP appears to influence APP endocytic trafficking and cellular distribution such that processing to A␤ and its extracellular release are enhanced (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Sehgal and colleagues reported that an extract of Withania somnifera induces a rapid clearance of amyloid pathology with a co-incident induction of LRP1 expression in liver [14]. Other proteins implicated in amyloidogenesis have been identified as interacting with LRP1 [15], such as apolipoprotien E (ApoE) and α2-macroglobulin. Both of these proteins are ligands of LRP1 and have been reported to mediate the clearance of Aβ [13,16-19].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of acquiring sulfatides by apoE particles is still unknown, which may be through a “kiss-and-run” mechanism or through a sulfatide carrier protein including apoE itself. In the working model, these nascent sulfatide-containing apoE-associated lipoprotein particles are then metabolized and degraded through an endocytotic pathway by neuronal cells possessing one or more members of the LDL receptor superfamily (e.g., LRP) [55, 56]. Under normal physiological conditions, the majority of the internalized sulfatides are catabolized to various degradation products (e.g., sulfate, galactose, trans -hexadecenal, sphingosine, etc.)…”
Section: Association Of Sulfatides With Apoe Particles In the Cnsmentioning
confidence: 99%